Chemical Composition of Aqueous Leaf Extract of Murraya koenigii - B Senthil Kumar, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Chemical Composition of Aqueous Leaf Extract of Murraya koenigii